Clinical Characteristics of Non-Smoking Chronic Obstructive Pulmonary Disease Patients: Findings from the KOCOSS Cohort. Issue 1 (31st December 2022) - Choi, Joon Young; Kim, Jin Woo; Kim, Yee Hyung; Yoo, Kwang Ha; Jung, Ki-Suck; Lee, Jin Hwa; Um, Soo-Jung; Lee, Won-Yeon; Park, Dongil; Yoon, Hyoung Kyu
Abstract: Chronic obstructive pulmonary disease (COPD) has been regarded as a disease of smokers, but the prevalence of non-smoking COPD patients have been reported to be considerable. We investigated differences in clinical characteristics between smoking and non-smoking COPD patients. We used data from the Korea COPD Subgroup Study (KOCOSS) database, which is a multicenter cohort that recruits patients from 54 medical centres in Korea. Comprehensive comparisons of smoking and non-smoking COPD patients were performed based on general characteristics, exacerbations, symptom scores, radiological findings, and lung-function tests. Of the 2477 patients included in the study, 8.1% were non-smokers and 91.9% were smokers. Non-smoking COPD patients were more likely to be female and to have a higher body mass index and lower level of education. Non-smoking COPD patients had more comorbidities, including hypertension, osteoporosis, and gastroesophageal reflux disease, and experienced more respiratory and allergic diseases. No significant differences in exacerbation rates, symptom scores, or exercise capacity scores were observed between the two groups. Smoking COPD patients had more emphysematous lung according to the radiological findings, and non-smoking patients had more tuberculosis-destroyed lung and bronchiectasis. Lung-function testing revealed no significant difference in the forced expiratory capacity in 1 sec between the two groups, but smokers had more rapid lung-function decline in the 5 years of follow-up data. We found differences in general characteristics and radiological findings between smoking and non-smoking COPD patients. No significant differences in exacerbation or symptom scores were observed, but decline in lung function was less steep in non-smoking patients. Supplemental data for this article is available online at https://doi.org/10.1080/15412555.2022.2053088 .